Barriers to entry, deregulation and workplace training - Andrea Bassanini; Giorgio Brunello (Institute for the Study of Labor (IZA), 2007)
We develop a theoretical and empirical analysis of the impact of barriers to entry on workplace training. Our theoretical model yields ambiguous predictions on the sign of this relationship. On the one hand, given the number of firms, a deregulation reduces profits per unit of output, and thereby reduces training. On the other hand, the number of firms increases, and so does the output gain from training, which facilitates the investment in training. Our numerical simulation shows that for reasonable values of the parameters a negative relationship prevails. We use repeated cross section data from the European Labour Force Survey to investigate empirically the relationship between product market regulation and training incidence in a sample of 15 European countries and 13 industrial sectors, which we follow for about 7 years. Our empirical results are unambiguous and show that an increase in product market deregulation generates a sizeable increase in training incidence.
urn:nbn:de:101:1-20080402287
Keywords: 330; Deregulierung; Markteintritt; Betriebliche Bildungsarbeit; Bildungsinvestition; Theorie; EU-Staaten